Development, Quality, and Production Parameters of In Vitro Embryo in Anatolian Water Buffaloes - Yılmaz, M. A.; Kaymaz, M.; Ergün, Y. (Faculty of Animal Science, IPB University, 2024)
The aim of the study was to determine in vitro embryo development, embryo quality, and in vitro embryo production (IVEP) parameters by using Anatolian water buffaloes (AWB) oocytes. In this study, 184 ovaries of 92 AWB obtained from slaughterhouses were used. The tissue culture medium (TCM-199) was used for in vitro maturation (IVM), Brackett & Oliphant (BO) medium for in vitro fertilization (IVF), and Charles Rosencrans 1 amino acid (CR1aa) medium for in vitro culture (IVC). A total of 395 oocytes (2.15 per ovary) were obtained from the ovaries. Frozen AWB sperm was used for fertilization. The number of cleavages at the 24th hour was 93 out of 302 (30.79%), the number of morulae and compact morula at the 96th hour was 53 out of 302 (17.55%), the number of blastocysts at 7th day was 29 out of 302 (9.60%), and the number of hatched blastocysts were 12 out of 302 (3.97%) on the 8th and 9th days. In the quality assessment of 29 blastocysts recovered on day 7 in IVC, 7 of them (24.13%) were of the code 1 quality, 9 of them (31.03%) were of the code 2 quality, 8 of them (27.50%) were of the code 3 quality, and 5 of them (17.24%) were classified as the code 4 quality. This study provides the first data on in vitro embryo development, embryo quality classification, and embryo production in AWB. As a result, the potential of oocytes AWB for IVEP has been revealed, and a scientific background has been provided for future studies.